2015
DOI: 10.1007/s10620-015-3691-z
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal and Hepatic Manifestations of Ebola Virus Infection

Abstract: Physicians must be vigilant for gastroenterologic manifestations of EVI for appropriate diagnosis and therapy. This work should stimulate clinicopathologic studies to improve the current understanding of the gastroenterologic pathophysiology. Endoscopy is currently not standardly recommended to evaluate diarrhea, nausea and vomiting, or abdominal pain associated with EVI due to potential risks, but may be considered for endoscopic therapy for active, life-threatening, GI hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…However, the mild elevation of bilirubin and the observation that AST levels were steadily much higher than those of ALT suggest that severe acute viral hepatitis is not a typical manifestation of EVD subsequent to EBOV. [35][36] Similar evidence has been reported in clinical studies in patients infected either with Sudan Ebola or [26] Taï Forest Ebola [37] and in animal model investigating pathogenesis of Bundibugyo Virus. [38] In conclusion, our study provides new evidence to support the hypothesis that EBOV may play a direct role in muscular damage and imbalance of coagulation system.…”
Section: Discussionsupporting
confidence: 73%
“…However, the mild elevation of bilirubin and the observation that AST levels were steadily much higher than those of ALT suggest that severe acute viral hepatitis is not a typical manifestation of EVD subsequent to EBOV. [35][36] Similar evidence has been reported in clinical studies in patients infected either with Sudan Ebola or [26] Taï Forest Ebola [37] and in animal model investigating pathogenesis of Bundibugyo Virus. [38] In conclusion, our study provides new evidence to support the hypothesis that EBOV may play a direct role in muscular damage and imbalance of coagulation system.…”
Section: Discussionsupporting
confidence: 73%
“…SARS-CoV-2 indirectly damages the digestive system through an inflammatory response chain (Musa, 2020). In addition, in other cases, Ebola and Lassa viral infections, it is said that GIT manifestations dominate at the beginning of symptoms (Sharma and Cappell, 2015), (Dongo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal symptoms are among the earliest, most common, and life-threatening clinical manifestations of EVD in humans [9]. In the 2014 outbreak in Western Africa, results of a study found that among patients admitted to the hospital with confirmed EVD, the most common clinical syndrome was one of gastrointestinal illness, intravascular volume depletion, and related complications [10].…”
Section: Introductionmentioning
confidence: 99%